Magnitude of pesticide use and its health effects among chilly farmers of Dammuru village, Bellary district, Karnataka, India - Janekunte, Dodda Basava; Doddaiah, Sunil Kumar (International Journal Of Community Medicine And Public Health, 2023)
Background: The second-largest industry in the world in terms of employment is agriculture. In other ways, working in agriculture is among the riskiest professions in the whole world. Each year, many farm workers have illnesses and workplace accidents. All people are exposed to some degree to pesticides, but farmers are more susceptible owing to the additional danger of occupational exposure. Methods: Purposive sampling was utilized in this cross-sectional research on chilly farm workers in the Dammuru village of Bellary district, Karnataka. An MS Excel spreadsheet was used to input the collected data, which was then analysed using SPSS version 23. Results: Out of 220 participants, 165 (or 75% of them) utilized items that were classified as class I (very hazardous), followed by 33 (or 15%) as class II (moderately hazardous), 16 (or 7.247%) as class III (somewhat hazardous), and 6 (or 2.72%) as class U (unsafe materials) (unlikely to present an acute hazard). The majority of the 220 individuals, 202 (91.81%) experienced health concerns, whereas the minority, 18 (8.18%), had no health issues. Conclusions: More than half of the survey participants reported having health issues, with a lack of information about the appropriate use of pesticides and improper use of protective gear being the major causes. 18 people (8.18%) did not have any health issues whereas 202 (91.81%) did.